2019
DOI: 10.1007/s00572-019-00905-2
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal frequency, physiological parameters, and yield of strawberry plants inoculated with endomycorrhizal fungi and rhizosphere bacteria

Abstract: Due to the impoverishment of agricultural and horticultural soils and replant diseases, there is a need to use bioproducts and beneficial microorganisms in order to improve the quality of soils and growth substrates. For this reason, research was undertaken to assess the impact of arbuscular mycorrhizal fungi and rhizosphere bacteria on changes in soil microbiology, the degree of colonization of plant roots by mycorrhizal fungi, selected physiological parameters, and fruit quality and yield of the strawberry c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 57 publications
3
16
2
1
Order By: Relevance
“…fungi. Our study did not confirm the results of the experiments conducted by other researchers, who observed that mycorrhization treatment increased the content of chlorophyll and carotenoids in the leaves of strawberries [40,60], cucumbers [56], and courgettes [61].…”
Section: The Influence Of Soil Preparations On the Growth Power Of Ap...contrasting
confidence: 99%
See 1 more Smart Citation
“…fungi. Our study did not confirm the results of the experiments conducted by other researchers, who observed that mycorrhization treatment increased the content of chlorophyll and carotenoids in the leaves of strawberries [40,60], cucumbers [56], and courgettes [61].…”
Section: The Influence Of Soil Preparations On the Growth Power Of Ap...contrasting
confidence: 99%
“…The authors found that the fungal population on the roots of the apple trees treated with the inoculant was over 50% greater than on plants which had not received the treatment. In the experiment conducted by Mikiciuk et al [40], the population was more than two times larger.…”
Section: The Influence Of Mycorrhizal Fungi and Trichoderma Spp On Th...mentioning
confidence: 95%
“…The assessment of the colonization degree of the roots by arbuscular mycorrhizal fungi was performed with the Trouvelot method ( Trouvelot et al, 1986 ). This method is based on the assessment of mycorrhizal frequency (F%) and relative mycorrhizal intensity (M%) that are calculated according to the formula described by Mikiciuk et al (2019) .…”
Section: Methodsmentioning
confidence: 99%
“…As a second application method, mycorrhiza was applied by soil spraying before first irrigation at the 6-8 leaf stage. To water one plant, 260 cm 3 of the suspension was used, which corresponds to a dose of 8.75 mg of the preparation per plant (Mikiciuk et al, 2019).…”
Section: Mycorrhiza Applicationsmentioning
confidence: 99%